Origin, early history and technology of the blue pigment in azulejos - Mimoso, J. (2016)
A few years ago I supervised an MSc dissertation on the blue cobalt pigment in Portuguese glazed tiles (azulejos). Looking for sources on the history of the cobalt pigment in Europe, I was directed to two papers published in German and one (unpublished) in Dutch. Those were: Beiträge zur Geschichte der Kobaltfarbe und ihre Verwendung in der Keramik (Contributions to the history of the cobalt colour and its use in ceramics) by Josef Horschik, an article originally published in Keramos nr. 85, pp. 119-142, 1979; Das Sächsische Blaufarbenwesen und der Handel mit Kobaltfarben – nach Unterlagen der Bücherei der Bergakademie Freiberg (The Saxony blue pigment and the trade in the cobalt colour - according to documents in the library of the Bergakademie of Freiberg) by Peter Hammer, a communication to the VII Int. Symp. ‘Cultural Heritage in Geosciences’. Scripta Geol. Spec. Issue 4, Winkler Prins & Donovan, 2004; and Zaans Blauw - van zaffer tot smalt naar ultramarijn (Zaan Blue - from zaffre to smalt to ultramarine) by Martin E. de Gruijl (written after 1993 and presumed unpublished). I translated the relevant parts of the papers for the benefice of the student and, finding in them information that was new to me, kept in mind that I would one day write down an abstract of the contents that might help other researchers to source historic and technical information on the pigment so famously used in Portuguese azulejos. The present text includes selected information abridged from those valuable texts to tell the whole story with incompatibilities between two of them critically assessed and edited, complemented with other information to encompass the relevant period for the pre-industrial production of azulejos in Portugal. A number of personal comments are added, particularly in the conclusive chapter.